Exploring protocol development: Implementing systematic contextual memory to enhance real-time fMRI neurofeedback - Fagerland Steffen Maude; Berntsen Henrik Røsholm; Fredriksen Mats; Endestad Tor; Skouras Stavros; Rootwelt-Revheim Mona Elisabeth; Undseth Ragnhild Marie (Journal of Electrical Bioimpedance)
The goal of this study was to explore the development and implementation of a protocol for real-time fMRI neurofeedback (rtfMRI-nf) and to assess the potential for enhancing the selective brain activation using stimuli from Virtual Reality (VR). In this study we focused on two specific brain regions, supplementary motor area (SMA) and right inferior frontal gyrus (rIFG). Publications by other study groups have suggested impaired function in these specific brain regions in patients with the diagnoses Attention Deficit Hyperactivity Disorder (ADHD) and Tourette’s Syndrome (TS). This study explored the development of a protocol to investigate if attention and contextual memory may be used to systematically strengthen the procedure of rtfMRI-nf.